2021
DOI: 10.3389/fpubh.2021.720512
|View full text |Cite
|
Sign up to set email alerts
|

Supportive or Confining? The Impact of War Metaphors From the COVID-19 Pandemic on Persons With Disabilities in Mainland China

Abstract: Ensuring the well-being of persons with disabilities (PWDs) is a priority in the public sector during the coronavirus disease 2019 (COVID-19) pandemic. To contain this unprecedented public crisis in China, a set of nationwide anti-epidemic discourse systems centered on war metaphors has guided the epidemic's prevention and control. While the public is immersed in the joy brought by the stage victory, most ignore the situation of the disadvantaged PWDs. Accordingly, this study adopts and presents a qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The PWDs, as a vulnerable population in the COVID-19 epidemic, probably suffered a greater negative impact on their daily routines, and their basic needs might be neglected [20]. However, quantitative data on the overall impact on the daily life of PWDs during the COVID-19 pandemic was still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The PWDs, as a vulnerable population in the COVID-19 epidemic, probably suffered a greater negative impact on their daily routines, and their basic needs might be neglected [20]. However, quantitative data on the overall impact on the daily life of PWDs during the COVID-19 pandemic was still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research on metaphors used to discuss the pandemic thus seems more reliable and relevant when considering the variables of context and relationship between interlocutors (i.e., Chen et al, 2021, with the focus on people with disabilities; for the contextual theory, Kövecses, 2005;Gibbs, 2017). However, few studies have examined the use of metaphors for pandemics in educational contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The social amplification of risk framework implies that concern about risk may be amplified when exposure to media coverage is increased ( 28 , 29 ). Especially, previous research has found that the war metaphor was widely used by many social media networks, such as the People's Daily, to report on COVID-19, which may create a sense of urgency and increase psychological stress ( 30 ). However, the concern and perceived risk may be attenuated when people are exposed to information provided by their trusted risk managers ( 27 ).…”
Section: Introductionmentioning
confidence: 99%